2001
DOI: 10.1179/016164101101199243
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cytokine cascade released by leukocytes in cerebrospinal fluid after subarachnoid hemorrhage

Abstract: Subarachnoid hemorrhage (SAH) elicits an inflammatory response in the subarachnoid space, which is mediated by the release of various cytokines. To assess their involvement in post-hemorrhagic complications, we determined the source and time-course of the release of inflammatory cytokines and acute-phase proteins in cerebrospinal fluid (CSF) following SAH. Concentrations of interleukin (IL)- 1beta, IL-6, transforming growth factor-beta1 (TGF-beta1) and C-reactive protein (CRP) in CSF of 36 patients with SAH we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
76
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(82 citation statements)
references
References 11 publications
5
76
0
1
Order By: Relevance
“…Interleukin-6 constitutes a strong stimulus for CRP synthesis by hepatocytes. 44,63 Additionally, IL-1, which has been implicated in the pathogenesis of cerebral vasospasm, also represents a strong stimulus for CRP synthesis. 63 Therefore, elevated concentrations of CRP may well be associated with an increased possibility of developing cerebral vasospasm and subsequently a DIND.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interleukin-6 constitutes a strong stimulus for CRP synthesis by hepatocytes. 44,63 Additionally, IL-1, which has been implicated in the pathogenesis of cerebral vasospasm, also represents a strong stimulus for CRP synthesis. 63 Therefore, elevated concentrations of CRP may well be associated with an increased possibility of developing cerebral vasospasm and subsequently a DIND.…”
Section: Discussionmentioning
confidence: 99%
“…11,55 Additionally, it has been demonstrated that CRP, an acute-phase protein, which is a highly sensitive indicator of inflammatory response, is produced by hepatocytes in response to increased production of IL-6. 6,44,63 Because IL-6 has been associated with the development of cerebral vasospasm, increased levels of CRP at the time of the patients' admissions and early in their postictal courses might have some predictive value in the early detection and proper management of vasospasm.…”
mentioning
confidence: 99%
“…In an experimental rat model of ICH, IL-6 up-regulation peaked 12 h after ICH and was related to glial activation (43). Early increase of IL-6 and IL-10 CSF concentrations after ICH (44) or severe traumatic brain injury (34,45,46) indicate its important role in mediating inflammatory response. In our study population, IL-6 and IL-10 concentrations in the CSF were found to be in a low range in all patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…4,9,19,22) Fasudil is believed to prevent Y. Suzuki et al delayed cerebral vasospasm and subsequent ischemic injury through the inhibition of Rho-kinase which reduces vasoconstriction, 3,12,13) occurrence of endothelial damage, 10,15,21) hyperviscosity, 6) and inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%